KERAPATAN DAN KEANEKARAGAMAN NEMATODA TANAH DI LAHAN BEKAS TAMBANG BATUBARA KECAMATAN CEMPAKA, KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Novy Etty Maretnoningrum; Abdul Gafur (Bioscientiae, 2008)
Density and biodiversity of soil nematodes in a discarded coal-mining site in CempakaSubdistrict, Banjar District, South Kalimantan Province, were studied in search for optimumdepth of soil samples taken for nematode community data. Three locations reflecting categories ofconditions were distinguishable in the study area: natural, partially damaged, and damaged. Fromeach location soil samples were taken up to 20 cm depth which were subsequently separated into0-10 and 10-20 cm. Comparisons of soil nematode density and biodiversity were made betweenthe two depth and the three locations. Statistical analyses suggested that natural location had thehighest density of nematodes, followed by the partially damaged and damaged locations. This isparallel to differences among the three conditions in organic-C and pH. However, no significantdifference in nematode density was found between the two depths of soil. Sample-based andindividual-based species accumulation curves showed that more species were found with moresamples and more individuals observed, and upper (0-10 cm) layer has more species than lower(10-20 cm) part of soils. Nevertheless, as the accumulation curves did not reach their asymptotes,more than 10 samples and 600 individuals are required to obtain more accurate informationregarding soil nematode biodiversity in the study area.